Biological functions and research progress of eIF4E - Chen, Xiaocong; An, Yang; Tan, Mengsi; Xie, Dongrui; Liu, Ling; Xu, Benjin (Frontiers in Oncology, 2023)
The eukaryotic translation initiation factor eIF4E can specifically bind to the cap structure of an mRNA 5' end, mainly regulating translation initiation and preferentially enhancing the translation of carcinogenesis related mRNAs. The expression of eIF4E is closely related to a variety of malignant tumors. In tumor cells, eIF4E activity is abnormally increased, which stimulates cell growth, metastasis and translation of related proteins. The main factors affecting eIF4E activity include intranuclear regulation, phosphorylation of 4EBPs, and phosphorylation and sumoylation of eIF4E. In this review, we summarize the biological functions and the research progress of eIF4E, the main influencing factors of eIF4E activity, and the recent progress of drugs targeting eIF4E, in the hope of providing new insights for the treatment of multiple malignancies and development of targeted drugs.